THE SOUTH USHKOTY ELUVIAL KAOLIN DEPOSIT IN THE SOUTHEASTERN ORENBURG REGION - Gorbachev B.F.; Sharapov A.F.; Lyadskii P.V.; Shmel'kov N.T. (My University, 2004)
The South Ushkoty eluvial kaolin deposit discovered and explored by the authors is situated 20 km away from the railway in the Dombarov district of the Orenburg region. The deposit is localized in the axial zone of the East Ural Uplift. Leucogranites of the Upper Ushkoty Pluton serve as bedrocks. The deposit comprises five lodes, among which the largest deposit has a reserve of 40 Mt. The lodes are erosion remnants of the well-developed linear-areal weathering zone related to the fragments of Mesozoic peneplain at the hypsometric level not lower than 360 m. Variation of the kaolin zone thickness, the entire weathering zone, and the deposit morphology is largely governed by the nearly meridional and northeastern faults. Two productive zones—the normal kaolin (kaolinite + quartz) zone and the alkaline kaolin (kaolinite + quartz + potassium feldspar and/or muscovite) zones—are recognized in the weathering profile of leucogranites of the Upper Ushkoty Pluton. The alkaline kaolin is of commercial significance as a complex raw material if the potassium oxide content is above 3.5%. The composition and properties of the concentrated kaolin meet the requirements of its traditional consumers (fine ceramic works, paper mills, and others). The discovery of the South Ushkoty deposit confirmed the previous forecast on considerable prospects of the Orsk Transural region for kaolin. We hope that this discovery will stimulate the further investigation and assessment of resources in the Mugodzhary kaolin-bearing subprovince.